DINAMIKA PERILAKU KOMUNIKASI REMAJA DI KELUARGA: KAJIAN BERDASARKAN FAMILY COMMUNICATION PATTERNS THEORY - Adhwa Kayla Safitri; Nurul Khoerunisa; Muhammad Fikri; Rifa Kamelia Khalda; Aulia Nur Nabilah; Hunainah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Family communication is one of the important factors supporting adolescents' social and emotional development. However, adolescents' communication behavior within the family does not always demonstrate uniform patterns. This study aimed to describe the dynamics of adolescents' communication behavior in the family based on the perspective of Family Communication Patterns Theory (FCPT). This study employed a qualitative approach with a descriptive method. The participants consisted of five adolescents selected through purposive sampling, while parents were involved as supporting informants. Data were collected through semi-structured interviews developed based on the dimensions of conversation orientation and conformity orientation. The data were analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that most families demonstrated a relatively high conversation orientation, characterized by routine communication, opportunities for discussion, and adolescents' involvement in certain decision-making processes. However, the level of emotional openness varied among participants. Some adolescents felt comfortable sharing their feelings and personal problems with their parents, while others preferred to confide in their peers. The study also found that family conformity was generally established through consensual communication rather than authoritarian practices. In addition, digital technology influenced the quality of family communication both as a facilitating and inhibiting factor in direct interaction. These findings indicate that the dynamics of adolescents' communication behavior are influenced by communication openness, the quality of emotional relationships, parenting patterns, and the process of negotiating values within the family.